Revitalization of Pandhalungan Creative Economy through Business Model Canvas Mapping for MSMEs in Serut Village, Jember Regency - Agung Budi Sulistiyo; Bayu Aprillianto; Bunga Maharani; Novi Wulandari Widiyanti; Gusti Ayu Wulandari; Muhammad Miqdad (AJAD : Jurnal Pengabdian kepada Masyarakat, 2023)
Serut Village, Jember Regency has great potential to develop local creative economic activities. Pandhalungan culture is a characteristic of local culture in the Jember Regency. MSMEs in Serut Village face a reasonably simple but crucial problem, namely the absence of determining the value proposition of the local creative economic activities, the traditional business model by relying on product distribution to middlemen, tends to produce products that are similar to products on the market. This activity aims to identify and develop a business model that is applied by several MSMEs in Serut Village using the Business Model Canvas (BMC) approach. This activity was focused on the form of counseling and assistance in the preparation of BMC for 6 (six) MSME actors in Serut Village. The implementation method of this activity consists of several stages, namely the preparation stage, the data collection stage, and the BMC preparation stage. The result of this service activity is that all MSMEs in Serut Village are able to identify and compile BMC mapping for their business. All MSMEs have determined the value proposition of their business.